The spoken knowledge of low literacy in patients with diabetes - OĞUZ, SIDIKA (ELSEVIER IRELAND LTD, 2011)
Aim: This research was planned descriptively and analytically to determine the diabetes knowledge of patients with low level of education diabetes. Methods: This study has been performed with 200 patients diagnosed with diabetes at least 3 months ago who were able to communicate, volunteered to participate in the study, had less than highschool education, and were at least 18 years of age. Data were collected through questionnaire and SKILLD (Individual Knowledge Scale), and is evaluated using ANOVA, chi-square and t-test. Results: The mean age of the participants was 54 +/- 15.104. There was difference between the time passed for the diagnosis of the diabetes and total SKILLD score averages (p = .009). SKILLD scores decreased as age and number of children increased (p = .003). SKILLD scores increased as education levels and diabetes duration increased (p < .0001). More patients with moderate level of education knew normal ranges of blood sugar and HbA1C compared to those with lower level of education (p < .0001). Besides, more patients with moderate level of education were aware of the optimum frequency to exercise, with a significant difference between the two groups (p < .0001). Conclusion: Diabetes knowledge increased with higher level education and younger ages, while the elderly and individuals with low level of education had insufficient knowledge on diabetes. (C) 2011 Elsevier Ireland Ltd. All rights reserved.
Keywords: Individual Knowledge Scale; Diabetes; Education; Nursing; SKILLD